The significance of the expression of cell proliferation and inflammation markers in the development of acquired middle ear cholesteatoma - Erdoglija, Milan; Grgurević, Uglješa; Cerović, Snezana; Jović, Milena; Baletić, Nenad; Sotirović, Jelena (Vojnosanitetski pregled, 2020)
Background/Aim. Permanent proliferation and periodical infection are the main clinical characteristics of acquired middle ear cholesteatoma. The aim of this study was to research immunohistochemical characteristics of the skin along with the cholesteatoma process in the nearby tissue. This research should influence further studying of etiology and development of acquired middle ear cholesteatoma. Methods. We investigated clinical, histological and immunohistochemical characteristics of cholesteatoma in 50 samples from operated patients with acquired middle ear cholesteatomas. We classified all samples according to their clinical characteristics of cholesteatoma such as bone destruction, presence of infection or cholesteatoma extension and histological characteristics of cholesteatoma such as keratinisation, inflammatory process and extracellular matrix proliferation. We used mouse monoclonal antibodies for proliferating cell nuclear antigen (MAbs for PCNA), Ki-67, COX-2, CD 4 and CD 8 lymphocytes to investigate the expression of those characteristics in the cholesteatoma and in the control skin tissue. Statistical analyses were performed using SPSS for Windows version 16.0 (SPSS, Chicago, IL, USA). We used the independent group t-test, Spearman’s correlation analysis and Mann-Whitney U test to analyze statistical analysis. Results. Expression of PCNA, Ki-67, COX-2 and CD 8 lymphocytes in more serious clinical picture of cholesteatoma was almost equal as in less serious clinical picture of cholesteatoma. There was statistically significantly higher concentration of inflammation marker CD 4 lymphocytes, both in the acquired cholesteatoma and in the skin of bony portion of the external auditory canal near fibrocartilaginous annulus in more serious clinical picture of cholesteatoma than in less serious clinical picture of cholesteatoma (p
Keywords: cholesteatoma; histology; immunohistochemistry; biological markers.